(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Salman Rushdie is considered one of the leading politicians of politically motivated fiction and an educated and often fearless commentator for the state of global politics today. He has written magical realistic novels with critical acclaim. The methods of magic realism, fantasy, and hallucination include his The Satanic verses (1989). Shame (1983) and Midnight Children (1981). It is a writing style that sometimes describes dreams as real and actual events as dreams. It implies the merging of the fantastic the daily transformation and the real, into the enormous and the imaginary. Magic realism combines realism and fantasy in a way which organically transmits magical elements from the depicted reality. Critics and readers see that a German art critic, Franz Roh, coined the term in the 1920’s to describe a rather surrealist painting of a group of German painters. Colombian Nobel Prize winner Gabriel Garcia Márquez is considered a prominent exponent and is generally recognised as the founding father of hallucination and magical realism.